Constraints of Math Teachers' in Conducting Action Research in the Philippines: Rights Analysis - Paolo Nino Valdez; Minie Rose Lapinid (UUM Press, 2015)
Purpose - This exploratory investigation examines the material and non-discursive constraints of Math teachers in conducting action research in the Philippines. It initially describes the contexts of participation of scholars situated in the periphery in knowledge production and teases out the apparent challenges faced in the successful conduct of research.   Methodology - Anchored on Lave and Wenger's concept of community of practice and legitimate peripheral participation, the study employs rights analysis as a means to determine the constraints   of the respondents in doing action research. Additionally, it traces the mechanisms of power that reinforce and reproduce these challenges. Data was obtained from 13 mathematics teachers employed in different schools under the Manila Archdiocesan and Parochial Schools Association (Mapsa). These teachers have varying work experiences and are teaching different grade levels. The respondents were systematically sampled since they are part of an action research course under the master's program in teaching math offered by the university.   Findings - Based on the findings, it is argued that due to the disempowering material, social and political conditions of these teachers, they may be considered as part of a hierarchy of peripheral participation since they possess limited opportunities for academic socialisation in the conduct of action research . Finally, this paper draws implications for the improvement of research training in periphery contexts.   Significance - With the increased interest in the socio-political dimension in the teaching and learning process, this work may be of interest to those engaged in conducting research training as well as other stakeholders in the academe to improve the conduct of action research in their respective educational institutions.